Complex Deoxidation Characteristics Analysis of Acid-family welding Electrode - Myong-Son Jo (Talenta Publisher, 2024)
We have selected products of complex deoxidtion formable in acid-system electrode and when ferromanganese and ferrosilicon were used as a deoxiderzer, the amount of oxygen and deoxidizer in deposited metal was analyzed and determined.